The effect of core stability exercise in reducing the risk of falling in the elderly at the work area of Kasian 1 public health center - Veni Fatmawati; Nova Mega Rukmana; Wibowo Septianto; Diyas Elsa Yuniarsih (Universitas 'Aisyiyah Yogyakarta, 2021)
Elderly is a condition that will be experienced by each people, where the age range is from 45 to 75 years. The process adds up age followed also by changes that occur in body systems either physiologically or pathologically in the presence of comorbidities. One of the processes that occurs is function cerebellum descends by starting with a balance disturbance and then the brain system, resulting in the risk of falling. Elderly experiencing falls can be affected by some things such as disorders of the brain system, self it self and the environment. A part from anatomical factors, there is also a lighting environment usually the elderly always wake up at night, if the environment is less lighting then the risk of falling is higher and if the condition of waking up, the concentration and muscle power cannot be optimal, resulting in decreased balance so that the risk of falling is higher. One way to maintain and minimize the risk can be done the core stability exercise. Benefits of core stability exercise is to strengthen the core as the support of the body so that the body can be stable. This type of research is experiment, using quasi experimental design with pre test and post test group design. The statistic test using Wilcoxon test. Sample of elderly at integrated healthcare center in Ngebel, totaled are 34 elderly. Elderly sample criteria age 60-74 years, do not use assistive devices and do not experience neurological disorders. Measure morse fall skale. The results of the homogeneity test show that the significance value (p) core stability exercise of 0.323, because of the significance of p 0.05 it can be concluded that the population is from the same variant or homogeneous. The calculation of the data normality test used the Shapiro-Wilk Test and is said to be normal if p 0, 05. Data normality test results 0.085. Hypothesis Test with willcoxon test because it has a normal and homogeneous data distribution in the group. From the test results obtained with a value of P = 0.034, meaning P 0, 05, so that there is an effect of core stability training on the risk of falling in the elderly.